1T/2H multi-phase MoS2 heterostructures: synthesis, characterization and thermal catalysis decomposition of dihydroxylammonium 5, 5′-bistetrazole-1, 1′-diolate. (14th June 2019) - Hu, Lishuang; Liu, Yang; Hu, Shuangqi; Wang, Yanping
Abstract : Dependence of ln( β / T p 2 ) on 1/ T p for TKX-50 and mixtures with 10 wt% 2H-MoS2 and 1T/2H-MoS2 . Abstract : MoS2 has attracted widespread attention in catalysis fields due to its unique physical and chemical properties. However, the effect of thermal catalysis applications on the thermal decomposition of energetic materials has not been reported yet. In this work, we demonstrated that 1T/2H multi-phase MoS2 heterostructures were fabricated through a facile hydrothermal reaction and discovered that the 1T/2H-MoS2 heterostructure possesses intrinsic catalytic activity for the thermal decomposition of energetic salts such as dihydroxylammonium-5, 5′-bistetrazole-1, 1′-diolate (TKX-50). The morphology, phase structure, and properties of the as-prepared catalysts were characterized and the catalytic effect of the multi-phase MoS2 heterostructure on the thermal decomposition of TKX-50 was evaluated. With 10 wt% 1T/2H-MoS2 heterostructure added, the peak temperature decreased from 250.8 °C to 198.5 °C, and the activation energy of TKX-50 from 220.07 kJ mol −1 to 133.04 kJ mol −1, respectively, which proved the promotion of the thermal decomposition of TKX-50 effectively. Furthermore, the possible catalytic mechanism for the TKX-50 decomposition was discussed. Under heat excitation, the conduction band electrons (ecb − ) and valence band holes (h + ) were excited and generated on MoS2 surfaces, which facilitated proton transfer from the H atom of NH3 OH + to the O atom of bistetrazole, and boosted the decomposition of TKX-50 further. This work may open up a new potential way for thermal catalysis application of MoS2 in the field of energetic materials.